THE IMPACT OF UNCERTAINTY IN GLOBAL GOLD AND OIL PRICES ON STOCK MARKET INDEX RETURNS: THE CASE OF THE MIST COUNTRIES - Pala, Fahrettin; Gorgun, Mehmet Ragip; Torusdag, Mustafa; Demirtas, Furkan; Barut, Abdulkadir (Kafkas University Iibf, 2025)
The current study explores the impact of global gold price uncertainty on the stock markets of the MIST countries: Mexico, Indonesia, South Korea, and T & uuml;rkiye. The study examined the crisis periods that started with the COVID-19 pandemic and continued with the Russia-Ukraine war, which caused uncertainty in gold and oil prices. Based on this, the study's data set consists of the daily closing prices between March 11th, 2020, and January 31st, 2023. The obtained data were analyzed using the Least Squares (ICC) and panel quantile regression (PQR) methods. There is a significant positive correlation between oil prices and oil volatility index with stock prices for the economies of T & uuml;rkiye, Indonesia, and Mexico, and a significant negative correlation between gold prices and gold volatility index with stock prices for developing countries. There is also a significant positive relationship between gold and oil prices and stock prices for the developed country, South Korea's economy. A significant negative correlation has also been proposed between gold and oil volatility indices and South Korean stock prices. This study provides a novel contribution to the literature by examining the impact of simultaneous global crises namely the COVID-19 pandemic and the Russia-Ukraine war-on the stock market indices of MIST countries through the lens of uncertainty in both gold and oil markets. While most existing studies focus on a single commodity or analyze crises in isolation, this research distinguishes itself by investigating the combined effects of two major global shocks and incorporating both price and volatility-based uncertainty indicators. The findings suggest that policymakers should develop country-specific and differentiated financial stability policies by taking into account the uncertainties in gold and oil markets during crisis periods.
Keywords: Covid-19; Russia-Ukraine war; gold volatility; oil volatility index; stock market index; index; oil prices; gold prices; MIST countries; Panel Quantile Regression